Stres Akademik Mahasiswa Ditinjau dari Motivasi Berprestasi, Kemampuan Adaptasi dan Dukungan Sosial pada Pembelajaran Daring di Masa Pandemi Covid-19 - Nanik Prihartanti; Partini; Wenny Nabila Inayati (Abdi Psikonomi, 2022)
This research focuses on academic stress which is a complex problem for college student in implementing online learning activities during the Covid-19 pandemic. Based on literature review, achievement motivation, adaptability, and social support are thought to be factors that influence college students academic stress. The purpose of this study was to determine the relationship: (1) achievement motivation, adaptability, and social support with college student academic stress, (2) achievement motivation with college student academic stress, (3) adaptability with college student academic stress, (4) social support with college student academic stress. This study uses a correlational quantitative approach and the population is college students S1 Muhammadiyah University of Surakarta. The sampling technique is cluster random sampling. Analysis of the data obtained using multiple regression analysis techniques with the help of Statistical Package for Social Sciences (SPSS) program. The results of this study indicate that: (1) there is a significant relationship between achievement motivation, adaptibility and social support with college student academic stress (p=0,000 ? 0,01), (2) there is a negative and significant relationship between achievement motivation with college student academic stress (rx1y= -0,154, p=0,000 ? 0,01), (3) there is a negative and significant relationship between adaptability with college student academic stress (rx2y= -0,493, p=0,000 ? 0,01), (4) there is a negative and significant relationship between social support with college student academic stress (rx3y= -0,111, p=0,036 ? 0,05).